2020
DOI: 10.2967/jnumed.120.252262
|View full text |Cite
|
Sign up to set email alerts
|

Optoacoustic Imaging of Glucagon-like Peptide-1 Receptor with a Near-Infrared Exendin-4 Analog

Abstract: Limitations in current imaging tools have long challenged the imaging of small pancreatic islets in animal models. Here, we report the first development and in vivo validation testing of a broad spectrum and high absorbance near infrared optoacoustic contrast agent, E4x12-Cy7. Our near infrared tracer (E4x12-Cy7) is based on the amino acid sequence of exendin-4 and targets the glucagon-like peptide-1 receptor (GLP-1R). Cell assays confirmed that E4x12-Cy7 has a high binding affinity (IC50 = 4.6 ± 0.8 nM). Usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…GLP-1 appears to mildly reduce action potentials in the alpha cell membrane at 1 mM glucose in isolated mouse alpha cells, and this effect is blocked by the GLP-1R antagonist exendin (9-39) ( 110 ), therefore suggesting the presence of GLP-1R, perhaps at a very low density, on a small proportion of alpha cells. The development of near infra-red and fluorescent analogues of GLP-1R ligands has enabled both in vivo ( 111 , 112 ) and high-resolution tissue imaging ( 113 , 114 ) of GLP-1R with high specificity, sensitivity, and reproducibility. Coupled with super-resolution microscopy, the fluorescent analog LUXendin645 revealed that 5% of alpha cells in murine islets expressed GLP-1R ( 114 ).…”
Section: Role Of Glp-1: Intra-islet or Intestinal?mentioning
confidence: 99%
See 1 more Smart Citation
“…GLP-1 appears to mildly reduce action potentials in the alpha cell membrane at 1 mM glucose in isolated mouse alpha cells, and this effect is blocked by the GLP-1R antagonist exendin (9-39) ( 110 ), therefore suggesting the presence of GLP-1R, perhaps at a very low density, on a small proportion of alpha cells. The development of near infra-red and fluorescent analogues of GLP-1R ligands has enabled both in vivo ( 111 , 112 ) and high-resolution tissue imaging ( 113 , 114 ) of GLP-1R with high specificity, sensitivity, and reproducibility. Coupled with super-resolution microscopy, the fluorescent analog LUXendin645 revealed that 5% of alpha cells in murine islets expressed GLP-1R ( 114 ).…”
Section: Role Of Glp-1: Intra-islet or Intestinal?mentioning
confidence: 99%
“…Created with BioRender.com. (111,112) and high-resolution tissue imaging (113,114) of GLP-1R with high specificity, sensitivity, and reproducibility. Coupled with super-resolution microscopy, the fluorescent analog LUXendin645 revealed that 5% of alpha cells in murine islets expressed GLP-1R (114).…”
Section: Role Of Glp-1: Intra-islet or Intestinal?mentioning
confidence: 99%
“…GLP1R/GIPR antisera, fluorescent agonists/antagonists and mouse models validated according to known cell localizations, enzyme self-labels, pharmacology, Glp1r/Gipr expression in enriched fractions, Glp1r − / − tissue, Glp1r − / − cells or GLP1R/GIPR-transfected cells. Reagent Name Source Reported cross-reactivity Validation GLP1R antibody [39] Mab 3F52 Iowa DSHB Human, primate GL1PR_BHK cells (and wild-type cells) GLP1R antibody [50] Mab 7F38 Iowa DSHB Human, Mouse, Rabbit, Rat Glp1r −/− mice GLP1R antagonistic antibody [ 27 , 48 ] Glp1R0017, GLP1R-APC University of Cambridge, Duke University Mouse Glp1r −/− mice, pharmacology, antibody co-localization GLP1R antibody [53] ab218532 Abcam Mouse, Rat Glp1r −/− mice GLP1R antibody * [18] MAB2814 RnD Systems Human SNAP_hGLP1R-U2OS (and wild-type cells) GLP1R agonist [ 57 , 58 , 60 , 61 ] E4 K12 -Fl, E4 ×12 -VT750, EP12-TR, EP12-BTMR, EP12-BTMR-X, EP40-BF, EP40-TR Harvard University Mouse, human GLP1R_HEK293 cells, MIN6, insulin reporter/staining, pharmacology GLP1R agonist [59] E4 x12 -Cy7 Memorial Sloan Kettering Cancer Center Mouse, human GLP1R_HEK293, insulin reporter, pharmacology GLP1R agonist [97] Ex4-Cy3, Ex4-Cy5 Novo Nordisk Mouse Glp1r −/− mice GLP1R agonist [ 65 , …”
Section: Glp1r/gipr Detection Pitfallsmentioning
confidence: 99%
“…The probe, termed E4 K12 -Fl, was able to label GLP1R_HEK293 cells, MIN6 beta cells and pancreatic islets in vivo, overlapping with an insulin reporter or insulin protein [57] . The same authors used click chemistry on a K12-substituted Ex4 to install an azide-functionalized VT750 or Cy7 fluorophores, showing utility for estimating in vivo beta cell mass in NOD type 1 diabetes and insulinoma xenograft models [ 58 , 59 ]. Demonstrating the importance of modification site, an Exendin4 (Ex4)-like neopeptide was substituted (or added) at positions 12, 27 and 40, before reaction with various NHS-fluorophores spanning green through near-infrared wavelengths [ 60 , 61 ].…”
Section: Fluorescent Agonist/antagonist Probesmentioning
confidence: 99%
“…A contrast agent such as ICG can absorb the energy from the incident laser in PAI. Part of the absorbed energy is converted to heat, causing a thermoelastic expansion, which generates an acoustic wave for detection. An advantage of ICG is that it is a water-soluble near-infrared (NIR) dye approved by the Food and Drug Administration (FDA) as a clinical imaging agent with a good safety profile. …”
Section: Introductionmentioning
confidence: 99%